Boris Nemtsov and Russian politics : power and resistance - Makarychev, A. S. (Andreĭ Stanislavovich); Yatsyk, Alexandra; Nemt͡sova, Zhanna (Soviet and post-Soviet politics and society, 2018)
In post-Soviet Russian politics, Boris Nemtsov is one of the most tragic figures'and not only because he was shot dead, at the age of 56, in close vicinity to the Kremlin, the locus of Russia's power. The 'transparency of evil' in this specific case was shocking: Nemtsov's murder was filmed by a surveillance camera. The videotape confirms the demonstrative and brazen character of the assassination. His death illuminated a core feature of the current regime that tolerates, if not incites, extralegal actions against those it considers to be 'foes, ' 'traitors, ' or members of 'the Fifth Column.' In this volume Boris Nemtsov is commemorated from different perspectives. In addition to academic papers, it includes personal notes and reflections. The articles represent a range of assessments of Nemtsov's personality by people for whom he was one of the leading figures in post-Soviet politics and a major protagonist in Russia's transformation. Some authors had direct experiences of either living in, or travelling to, Nizhny Novgorod when Nemtsov was governor there. The plurality of opinions collected in this volume matches the diversity and multiplicity of Nemtsov's political legacy.